MICROWAVE METHOD FOR DETERMINATION OF DIELECTRIC PROPERTIES OF LIQUIDS - N. A. Pevneva; A. V. Gusinskii; A. L. Gurskii (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The waveguide method for determining the dielectric constant of materials was considered with using a panorama meter of the reflection and transmission coefficients. The influence of the waveguide channel’s parameters (linear dimensions, the reflection coefficients of materials) on the accuracy of the permittivity in the microwave range was assessed.